Comparation of Alterantive Policy Rules in a Structural Model of the Czech Republic - Hlédik, Tibor (2009)
The main goal of this thesis has been a study of alternative policy rules in a small structural model calibrated to capture the Czech economy. After the overview of the historic development of economic theory and structural modeling we have specified a small open economy model that has served as a main technical tool for the analysis. The model represents a framework, where forward-looking model-consistent expectations are formed with respect to the development of the exchange rate and interest rates. Inflation expectations are forward looking too with some nominal rigidities in inflation dynamics. The model's structure is relatively simple. The IS curve captures the dynamics of real GDP, that exhibits real rigidity, motivated by habit formation or investment adjustment costs. In our specification the real GDP is a function of (the deviation of) real XR, real IR and foreign demand (from corresponding equilibrium levels). The Phillips-curve is based on the F-M type wage setting behavior, therefore it enables to consider domestic prices, that are modeled as mark-ups over wages. CPI inflation then consists of domestic, imported and administered inflation, including the effect of any indirect taxes changes. The exchange rate is modeled by the UIP arbitrage condition. Exchange rate expectations are forward-looking, but with some inertia in expectation formation. Interest rates with one year maturity are also modeled as an arbitrage condition on the money market, they are fully model-consistently forward looking. The model is closed by a Taylor-type forward-looking policy rule. The interest rate exhibits some inertia and feeds back from deviation of inflation from target and output from its equilibrium. The specification (parameterization) of the rule is general enough to examine CPI and domestic inflation targeting.